Characterization of the dynamics of hepatitis B virus resistance to adefovir by ultra‐deep pyrosequencing. Issue 3 (30th July 2013) - Rodriguez, Christophe; Chevaliez, Stéphane; Bensadoun, Paul; Pawlotsky, Jean‐Michel
<x xml:space="preserve">Abstract</x> Hepatitis B virus (HBV) resistance to nucleoside/nucleotide analogs is frequent. Ultra‐deep pyrosequencing (UDPS) is a powerful new tool that can detect minor viral variants and characterize complex quasispecies mixtures. We used UDPS to analyze the dynamics of adefovir‐resistant HBV variants in patients with chronic HBV infection in whom adefovir resistance occurred during treatment. Amino acid substitutions known to confer resistance to adefovir were detected at baseline in most patients. The dynamics of adefovir‐resistant variants were complex and differed among patients as a result of evolving differences in variant fitness. UDPS analysis revealed successive waves of selection of HBV populations with single and multiple amino acid substitutions. Adefovir‐resistant variants were partially inhibited by lamivudine, but remained fit in its presence. Conclusion: Substitutions conferring HBV resistance to nucleoside/nucleotide analogs exist before treatment, and that the dynamics of adefovir‐resistant populations are much more complex and heterogeneous than previously thought and involve thus far unknown amino acid substitutions. The UDPS‐based approach described here is likely to have important implications for the assessment of antiviral drug resistance in research and clinical practice. (Hepatology 2013;53:890–901)